Anxiety Through Id, Ego, Superego Defense Mechanisms The Last House On The Left Movie Script By Mark Haslett - Dewi Saputri Meiranti; Sudirman Maca; Asyrafunnisa Asyrafunnisa (Fakultas Sastra, Universitas Bosowa, 2023)
The anxiety that occurs in the main characters and how the main characters overcome their anxiety through defense mechanisms. The study aimto analyze the anxiety factors that causes many psychological problems from the main characters and to describe the main characters defense mechanism to overcome their anxiety in the movie script The Last House on The Left by Mark Haslett. The main data of this research was The Last House on The Left movie script by Mark Haslett published by Midnight Entertainment in 2009 amounted 97 pages. Meanwhile, the supporting data came from several library sources, namely books, journals and other things that are relevant to support this research. The data were obtained by reading the movie script itself, taking notes on important things related to the main research objectives, analyzing the collected data, and drawing conclusion.In analyzing the data, the writer used psychological theory by Sigmund Freud. The results of this study showsthat the main characters Mari and Justin have 3 factors of anxiety, namely neurotic, realistic, and moral anxiety.. There were also some defense mechanism that the main characters used to overcome their anxiety was repression, compensation, sublimation, reaction formasi, rationalization, displacement, altruism, and undoing.